Проблемы предоставления в аренду нежилой недвижимости, находящейся в имущественной казне города Москвы (Путеводитель предпринимателя)
The article overviews a place, urgency and economic efficiency of rent relations in a control system of a state ownership. The author designates the practice of transfering the objects of uninhabited fund of Moscow in rent and reflects the competitive component of rent relations. Also the author reveals the basic problems of granting in rent uninhabitable Moscow property and offers their decision through business and government interaction on the partner beginnings.